MODIS-derived interannual variability of the equilibrium-line altitude across the Tibetan Plateau - Marinka Spiess; Christoph Schneider; Fabien Maussion (Annals of Glaciology, 2016)
Using the Moderate Resolution Imaging Spectroradiometer (MODIS) Level 1 radiance Swath Data (MOD02QKM) with a spatial resolution of 250 m, we derive snowlines during July–September 2001–12 for several mountain ranges distributed across the Tibetan Plateau (TP). Radiance bands 1 and 2 are projected to the study area and processed automatically. The discrimination between snow and ice is done using a k-mean cluster analysis and the snowlines are delineated based on a fixed percentile of the snow-cover altitude. The highest transient snowline altitude is then taken as a proxy for the equilibrium-line altitude (ELA). In the absence of measured glaciological, meteorological or hydrological data, our ELA time series enable better understanding of atmosphere-cryosphere couplings on the TP. Interannual ELA variability is linked to local and remote climate indices using a correlation analysis. Southerly flow and higher temperatures are linked with a higher ELA in most regions. Eastern and Trans-Himalayan sites show positive correlations between winter temperatures and ELA. As winter temperatures are substantially below zero, this suggests an enhancement of winter sublimation as opposed to a reduction in accumulation. It appears that large-scale atmospheric forcing has varying and sometimes opposite influences on the annual ELA in different regions on the TP.